2020
DOI: 10.1021/acs.est.9b07458
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Scale Analysis of the Energy–Land–Water Nexus: Nitrate Leaching Implications of Biomass Cofiring in the Midwestern United States

Abstract: As scientists seek to better understand the linkages between energy, water, and land systems, they confront a critical question of scale for their analysis. Many studies exploring this nexus restrict themselves to a small area in order to capture fine-scale processes, whereas other studies focus on interactions between energy, water, and land over broader domains but apply coarse resolution methods. Detailed studies of a narrow domain can be misleading if the policy intervention considered is broad-based and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Further, the firms' decisions are affected by the adoption decisions of other firms, both through their competition in the electricity market clearing and through competition for local biomass supply, which affects the biomass price. The model framework builds on previous work that combined a high-resolution representation of the power sector with interaction between the electricity and biomass markets to evaluate the impact of a co-firing mandate on a coupled energy-water-land system (Sun et al, 2020). Here we provide a brief overview of the main features of the framework; see Sun et al (2020) and the Appendix for more details on each model component.…”
Section: Modeling Frameworkmentioning
confidence: 99%
“…Further, the firms' decisions are affected by the adoption decisions of other firms, both through their competition in the electricity market clearing and through competition for local biomass supply, which affects the biomass price. The model framework builds on previous work that combined a high-resolution representation of the power sector with interaction between the electricity and biomass markets to evaluate the impact of a co-firing mandate on a coupled energy-water-land system (Sun et al, 2020). Here we provide a brief overview of the main features of the framework; see Sun et al (2020) and the Appendix for more details on each model component.…”
Section: Modeling Frameworkmentioning
confidence: 99%
“…Ethanol production from cellulosic feedstocks has mainly come from crop residues, which has been shown to have deleterious effects on soil and cropping systems, including N loss. Depending on where they are grown, which crops they displace, and how they are managed, perennial energy crops have the potential to reduce N loss to water at a field, watershed, and regional scale while meeting ethanol production goals. It has been shown that the economic incentives for producing energy crops would likely lead to production on land described as marginal with low opportunity costs of conversion from existing uses to energy crops . In other words, perennials are unlikely to displace land currently used for corn and soybean production.…”
Section: Introductionmentioning
confidence: 99%
“…However, they prescribed land use change exogenously (i.e., forced perennials to replace cropland across the MARB evenly) and did not consider whether conversion of land under corn to miscanthus or switchgrass production would be economically viable. To endogenously determine (i.e., dynamically predict) the economic and biophysical water quality implications of policy-driven land use change for the MARB, an integrated modeling approach is needed …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations